Clinical spectrum of individuals with de novo EBF3 variants or deletions. Issue 10 (29th May 2021) - Nishi, Eriko; Uehara, Tomoko; Yanagi, Kumiko; Hasegawa, Yuiko; Ueda, Kimiko; Kaname, Tadashi; Yamamoto, Toshiyuki; Kosaki, Kenjiro; Okamoto, Nobuhiko
Abstract: Hypotonia, ataxia and delayed development syndrome (HADDS) (MIM#617330) is a neurodevelopmental disorder caused by heterozygous pathogenic variants in EBF3 (MIM; 607, 407), which is located on chromosome 10q26, and was first reported in 2017. To date, missense, nonsense and frameshift variants have been reported as causes of HADDS, and EBF3 pathogenic variants have been predicted to result in nonsense‐mediated mRNA decay and haploinsufficiency. It was also reported that total deletion of EBF3 associated with a 10q26.3 microdeletion also causes HADDS symptoms, supporting the concept that HADDS results from haploinsufficiency of EBF3 . Here, we report eight unrelated individuals with heterozygous pathogenic variants of EBF3 or haploinsufficiency of EBF3 due to 10q26 deletion, who exhibit clinical findings including craniofacial features of HADDS. In a detailed examination of clinical manifestations in this study, revealed that neurogenic bladder was diagnosed in infancy (the median 6.5 months), was more frequent than previously reported, and required cystostomy in all but one case. For psychomotor delay, it was also found that their motor/skills values were significantly lower than their cognition/adaptation values ( p = 0.0016; paired t‐test). Therefore, that HADDS is a recognizable syndrome that shares its characteristic facial features, and that neurogenic bladder diagnosed in infancy and psychomotor delay with marked delay in motor/skills are noteworthy findings in the diagnosis and management of individuals with HADDS.